2008
DOI: 10.1074/jbc.m707238200
|View full text |Cite
|
Sign up to set email alerts
|

Differential Modulation of Akt/Glycogen Synthase Kinase-3β Pathway Regulates Apoptotic and Cytoprotective Signaling Responses

Abstract: We have previously reported that specific dopamine agonists mediate protection against apoptosis induced by oxidative stress by activating the D 2 receptor-coupled phosphoinositide 3-kinase (PI-3K)/Akt pathway. In the present study we examined the downstream effectors of PI-3K/Akt signaling and their role in cell death after oxidative stress and protection provided by ropinirole, a D 2 receptor agonist in PC12 cells and primary cultures of dopamine neurons. Ropinirole treatment was associated with rapid transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 60 publications
(60 reference statements)
1
53
0
1
Order By: Relevance
“…The rat pheochromocytoma neuron-like PC12 cells have been widely used as a model to study H 2 O 2 -induced oxidative stress (Li et al 2008;Nair and Olanow 2008;Aliaghaei et al 2014), therefore, we started our investigation of PC neuroprotection with this model. To examine the effects of different concentrations of H 2 O 2 on cell viability, PC12 cells were exposed to various concentrations of H 2 O 2 (50 to 1000 μM) for 24 h, and cell viability was determined by CalceinAM assay.…”
Section: Resultsmentioning
confidence: 99%
“…The rat pheochromocytoma neuron-like PC12 cells have been widely used as a model to study H 2 O 2 -induced oxidative stress (Li et al 2008;Nair and Olanow 2008;Aliaghaei et al 2014), therefore, we started our investigation of PC neuroprotection with this model. To examine the effects of different concentrations of H 2 O 2 on cell viability, PC12 cells were exposed to various concentrations of H 2 O 2 (50 to 1000 μM) for 24 h, and cell viability was determined by CalceinAM assay.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier studies that utilized GSK-3b inhibitor VIII were performed in in vitro cell culture systems (Nair and Olanow 2008) but in vivo rat models have also demonstrated the efficacy of this agent when administered through the external jugular vein (Koh et al 2007(Koh et al , 2008. Although a few studies have shown a benefit of nonselective GSK inhibitors in stroke, these were limited by lack of pharmacological specificity of the inhibitor used, and the mechanism was not clearly identified.…”
Section: Discussionmentioning
confidence: 99%
“…Although the PI3-K/Akt pathway is known to be activated by native D 2 and D 3 receptors in primary cultures of striatal neurons (Brami-Cherrier et al, 2002), by D 2L and D 3 receptors stably expressed in PC12 cells (Nair and Sealfon, 2003;Nair and Olanow, 2008;Chen et al, 2009), and by GFPtagged D 3 receptors expressed in EM4 cells (Zapata et al, 2007), the intracellular cascades leading to recruitment of Akt remain to be characterized. Furthermore, although activation of D 2 receptors expressed in PC12 and CHO cells (Welsh et al, 1998;Nair and Olanow, 2008) enhanced phosphorylation of GSK-3␤ and p70S6 kinase, there is otherwise little information about D 2 receptor-recruited pathways that interact with Akt signaling, such as Wnt and ␤-catenin. Information is even sparser for D 3 receptors, because there is only fragmentary evidence that stimulation leads to the phosphorylation of Akt and GSK-3␤ (Zapata et al, 2007;Chen et al, 2008).…”
mentioning
confidence: 99%